Hypertension is associated with dysfunction of both peripheral and central auditory system - Przewoźny, Tomasz; Gójska-Grymajło, Anna; Kwarciany, Mariusz; Graff, Beata; Szmuda, Tomasz; Gąsecki, Dariusz; Narkiewicz, Krzysztof (Journal of hypertension, 2016)
OBJECTIVES: Arterial hypertension negatively influences the peripheral auditory system, causing sensorineural hearing loss. Much less is known about the detrimental effects of hypertension on the central auditory functions. METHODS: We tested 32 arterial hypertension patients and 32 age and sex-matched healthy volunteers with the expanded tonal audiometry (0.125-12.5 kHz), distortion product otoacoustic emissions (0.75-8 kHz), horizontal minimum audible angle test for eight azimuths with binaural stimulation and the random gap detection test. RESULTS: Peripheral hearing of the hypertensive patients was impaired in comparison with the controls within all audiometric frequencies (0.125-12.5 kHz) and within specific groups of frequencies. Distortion product otoacoustic emission results were significantly lower for frequencies 4 (P = 0.04) and 6 kHz (P < 0.001). The sound localization ability in the horizontal minimum audible angle test was significantly worse in the hypertensive patients in the 0°, 45°, 90°, 135°, and 270° azimuth when the interaural pure tone average (0.5-1-2 kHz) was set less than 20 dB hearing level (P < 0.05), and in the 0°, 90°, 225°, and 270°azimuth when the binaural pure tone average (0.5-1-2 kHz) was set 20 dB or less hearing level (P < 0.05). Gap detection thresholds in the random gap detection test did not differ between the two groups. CONCLUSION: Arterial hypertension is independently related to the damage of the peripheral part of the auditory system resulting in high-frequency hearing loss. Hypertensive disturbances of central auditory processing are more discrete and concern the spatial hearing resolution.
Keywords: dospělí; hypertenze; Female; Otoacoustic Emissions, Spontaneous; Hearing Loss, Sensorineural; Adult; ženské pohlaví; lidé; studie případů a kontrol; audiometrie čistými tóny; Hypertension; Male; Case-Control Studies; lidé středního věku; otoakustické emise spontánní; mužské pohlaví; percepční nedoslýchavost; Middle Aged; Audiometry, Pure-Tone; Humans